The business of transportation - Prokop, Darren (Santa Barbra, CA Praeger)
Preface 1.Transportation in business decision-making / Darren Propok -- 2.The Motor carrier business / Thomas M. Corsi -- 3. The Railroad business ? Michael W. Babcock -- 4. The Airline business /Ryan Leick and John G. Wensveen -- 5. The Ocean shipping business / James Nolan and Ziad Ghaith -- 6. the Oil and refined products pipeline business / Adrianne Cook -- 7. Intermodalism : competition or cooperation?/ Bart Wiegmans 8. Transportation brokers and freight forwarders / Cidny Amos 9.Prices and costs / Kevin E. Henrickson and Welsey W. Wilson 10. Location and network planning in transportation / Jake M. Kosior
A 2 volumes set the library has volume 1 only
Keywords: Transportation; TRANSPORT; BUSINESS; ECONOMICS